YY1 facilitates the association of serum response factor with the c-fos serum response element. - Natesan, S (1995)
YY1 is a multifunctional transcription factor that acts as an activator or repressor in different contexts. YY1 binds to multiple sites in the mouse c-fos promoter, inducing at each site a sharp DNA bend. Binding of YY1 to a site situated between the cyclic AMP response element (CRE) and the TATA box bends the DNA in a way that interferes with the interaction of proteins bound at the CRE and TATA elements, resulting in repression of transcription. Here, we show that binding of YY1 to a different site in the c-fos promoter has a different result. Binding of YY1 to the c-fos serum response element (SRE) enhances the binding of serum response factor (SRF). This enhancement requires the binding of YY1 to SRE DNA. YY1 and SRF can cooccupy the SRE at least transiently. In the region of overlapping contact, YY1 contacts DNA in the major groove, while SRF contacts DNA in the minor groove. YY1 also enhances the association of SRF with the SRE in transfected insect cells. Thus, although YY1 induces similar structural changes in DNA at different binding sites, it can have distinct local effects on protein-DNA and protein-protein interactions. These data support a general role for YY1 in the building of highly organized promoter complexes.